(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employees are now a highly important part of every organization. Employees’ performances are one of the keys to achieving business goals. Employees are everything to your business, but if your employees are not performing, it undermines all the work you’ve put into your business. Having great employees can help achieve organizational goals, as stated by Sineriz M.H. (2019). The study revealed that most of the employees strongly agree with the factors that affect employees’ performances in Concentrix Bridgetown West, Quezon City. Based on the assessment of Effectiveness in management, the respondents strongly agree with 3.69 for males and 3.70 for females. The male strongly agrees with 4.29, and the female agrees with the 3.11 weighted mean that tools and technology can affect employees’ performances. Based on the assessment of the Physical Work Environment, the most affected are females, with 4.00 and 3.99 for males, and the two groups strongly agreed. Moreover, in the assessment of the Digital Work Environment, the male strongly agrees with 4.24 and the female with 3.06. It revealed that there is a significant difference between the two groups. The researchers recommend a reward for the good performance of employees, like a certificate for the top performing employees of the month, because it will make employees perform better and will result in effective management. Providing enough advanced tools and technology to be used by the employees and fixing the PCs that are not working well and running slowly to increase employees’ performances. Direct communication can solve the ethical problems of employees. Using cloud backup to restore or recover the data needed for the future to organize the files of the organization, and lastly, conducting a review of past and present performance of the employees to evaluate the work and improve what needs to be improved.